Information sharing and credit: Firm-level evidence from transition countries - Martin Brown; Tullio Jappelli; Marco Pagano (Goethe University Frankfurt, Center for Financial Studies (CFS), 2008)
We investigate whether information sharing among banks has affected credit market performance in the transition countries of Eastern Europe and the former Soviet Union, using a large sample of firm-level data. Our estimates show that information sharing is associated with improved availability and lower cost of credit to firms. This correlation is stronger for opaque firms than transparent ones and stronger in countries with weak legal environments than in those with strong legal environments. In cross-sectional estimates, we control for variation in country-level aggregate variables that may affect credit, by examining the differential impact of information sharing across firm types. In panel estimates, we also control for the presence of unobserved heterogeneity at the firm level, as well as for changes in macroeconomic variables and the legal environment.
urn:nbn:de:hebis:30-60389
Keywords: D82; G21; G28; O16; P34; 330; Information Sharing; Credit Access; Transition Countries; Investition; Kreditmarkt; Bankgeschäft; Kreditwürdigkeit; Informationsbeschaffung; Informationsaustausch; Transformationsstaaten